Identification of Novel USH2A Mutations in a Consanguineous Chinese Family With Usher Syndrome - Wang, Haolin; Wei, Bo; Guo, Jiaxin; Wu, Xiawei; Zou, Tongdan; Wang, Ting; Zhang, Tiantian; Gong, Bo; Hao, Jilong; Zhang, Houbin; Wang, Le (Human mutation, 2025)
Usher syndrome (USH) is a rare genetic disease characterized by sensorineural deafness and blindness called retinitis pigmentosa, and it is inherited in an autosomal recessive pattern with a prevalence of four to 17 per 100,000 people worldwide. In this study, a consanguineous Chinese family with USH, including two affected individuals and five unaffected individuals, was recruited. All subjects received an ophthalmic examination and an auditory examination. The two USH patients exhibited severe early-onset hearing and vision loss. DNA samples from the two USH patients were analyzed using whole-exome sequencing. A novel homozygous frameshift mutation (NM_206933.4:c.6379_6380delinsC, p.G2127Pfs∗25) in , resulting in a truncated protein lacking 3051 amino acids, was identified in the proband. In addition, novel compound mutations in (one allele harboring NM_206933.4:c.9958G>T, p.G3320C; NM_206933.4:c.8284C>G, p.P2762A; and the other NM_206933.4:c.6379_6380delinsC; p.G2127Pfs∗25) were identified in the other affected individual. In silico analysis predicts that while the p.G3320C mutation has little impact on the local structure around the mutation site, the p.P2762A substitution may alter the protein's interaction with its binding partners. In addition, p.G2127Pfs∗25 causes a truncation of a major portion of the protein that severely disrupts the protein structure and results in the loss of its function. In conclusion, this study identified novel USH mutations in and expanded the spectrum of disease-associated variants in the gene, which will promote the molecular screening of genetic mutations in USH patients.